Estudo experimental do escoamento bifásico ar-água em uma bomba centrífuga radial - Cubas, Jhoan Miguel Cubas (2017)
Over the last years the use of electric submersible centrifugal pumps (ESPs) has become the second most widely used artificial elevation method in the oil industry. As the typical production of submarine oil wells consists of mixtures containing oil and gas, the centrifugal pumps are subjected to operate with two-phase flow. The presence of free gas in the flow causes instabilities and degradation of the pump pressure-rise curve. This degradation becomes severe when the surging phenomenon occurs, which is characterized by large gas accumulations inside the impeller, with its initiation identified as the point in the pressure-rise curve from which the performance falls abruptly with the decrease of the liquid flow rate. Depending on the intake gas fraction, the rotor channels can be completely blocked (gas locking), causing the liquid flow rate and the pressure-rise to be almost null. Therefore, knowledge of operating conditions and flow patterns linked to the occurrence of surging for proper pump operation is critical. In this scenario, the present work aims to evaluate the performance of a centrifugal pump operating with two-phase air-water flow. To this end, the pressure-rise curves of a conventional two-stage centrifugal pump with radial rotors were measured. The tests were done using water and air as working fluids, with volumetric gas fractions between 0 and 10%, rotational speeds between 300 and 600 rpm, water flow rates between 0.2 and 1.5 times the best efficiency point and a suction pressure of 160 kPa. At the same time, different flow patterns were identified inside the rotor under different operating conditions. For this purpose, the pump casing and the original rotor of its first stage were replaced by equivalent transparent pieces, which allowed photographing the gas distribution inside the pump with the help of a high-speed camera. In addition to using the homogeneous (non-slip) model as a reference to calculate the inlet gas volume fraction in each test, a wire mesh sensor was installed in the intake pipe in order to measure the actual void fractions, which were later compared with the results from the homogeneous and the drift flux models. The images obtained were associated with the instabilities observed in the performance curves of the pump, as a way to understand the phenomena related to the performance degradation in two-phase flow operation, especially under surging conditions. This procedure, together with the measurement of the actual gas volume fractions in the pump intake, not just contributes to the understanding of gas-liquid flows in pumps, but also provides an interesting source of data for input and validation of theoretical and numerical models for other investigations.